About some ethical perplexities of modern medicine / O nekaterih etičnih zadregah sodobne medicine - Trontelj, Jože (Acta Medico-Biotechnica, 2021)
I greatly appreciate being invited to a gathering of such eminent researchers. A series of international conferences entitled “Medicine and Law” organized by the University of Maribor has enabled dialogue between professionals in medicine and in law. The benefits go beyond this dialogue. The conferences have been an opportunity for self–reflection in both areas and for in-depth analyses of some of the important ethical and legal questions of our time.